DEGRADATION OF KERATIN CONTAINING WASTES BY BACTERIA WITH KERATINOLYTIC ACTIVITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The aim of this study was to select keratin-degrading bacteria from JSC “Biocentras” collection and poultry processing plant wastewater, and to study their ability to degrade chicken feathers. Isolated from poultry processing plant wastewater bacteria was grown in basal media with feathers meal and showed high keratinolytic activity and protein content throughout the cultivation time. Bacterial strains B. licheniformis 511, B. subtilis I1, B. subtilis 717, and B. subtilis 103 suggested strongly of bacteria that produces keratinolytic activity in the cell free culture supernatants. The obtained results showed that maximum activity of keratinase is a function of cultivation time by the bacteria tested. B. subtilis 103 reached to its maximum level of keratinase production (152 U/mL) after 24 hrs, when over bacteria (148-242 U/mL) after 48 hrs. The good ability of selected bacteria to degrade feathers was detected. The best biodegradation of feathers was obtained using B. subtilis I-1. Over bacillus good degraded feathers as well.